Effect of subcutaneous oxycodone for end-stage heart failure due to severe aortic stenosis — A case report. Issue 6 (June 2018) - Futami, Shutaro; Ishikawa, Joji; Arima, Yukari; Mogami, Yukiko; Nemoto, Yoshiko; Tanaka, Jun; Saito, Eiichi; Harada, Kazumasa
Abstract: It is difficult to manage the symptoms of patients who are dying of end-stage heart failure (HF). Opioids are sometimes required to relieve their symptoms in addition to oxygen therapy and medical management. Oxycodone is a μ receptor agonist that is known to be a safer opioid than morphine in patients with chronic kidney disease (CKD) because its metabolites have weak pharmacological activity. We treated a 99-year-old woman who had end-stage HF (secondary to severe aortic stenosis) and CKD. It was also difficult to maintain an intravenous line because of severe edema. We administered oxycodone subcutaneously and successfully alleviated her severe symptoms without severe adverse effects of opioids until a few days before her death. We report this case and discuss the possibility of using subcutaneous oxycodone as a new palliative care strategy in patients with end-stage HF. <Learning objective: We report the management of chest symptoms of an elderly patient with end-stage heart failure (HF) due to severe aortic stenosis by subcutaneous infusion of oxycodone. This method has a possibility to alleviate chest symptoms of end-stage HF with less severe adverse effects until a few days before death than morphine, and may be useful to manage the symptoms even in patients with severe edema. Further investigation will be required to compare subcutaneous oxycodone with intravenous morphine.>